Power supply (voltage regulator) / Aaron Kevin Isaac - Isaac, Aaron Kevin (2005)
How do you control everything? By limiting freedom of course. In this case, my project will focus on the voltage regulator, where its job is to limit the output voltage. This is to meet certain requirements of a secondary circuit. For example, we don't want to activate the ceiling fan at 240V right? The fan will wear out faster and the tremendous output is too much for us. That's where the voltage regulator comes in. We can limit the speed of the ceiling fan to suit our needs. In addition to that, this concept is applied everywhere, from the brightness of an LCD (liquid crystal display), the speed of a grinder, drill, volume control etc. My project is actually used in every electrical appliance. Why? To control the device, to put it quite simply. I lowcver. this project is extended. I w ill connect a digital panel meter to it so the user can adjust the voltage output in such a precise way. Putting stickers on knobs is not accepted these days. With this advantage, users can record down the output readings and perform advanced calculations more cnsils with t lie adequate accuracy of the panel meter. In conclusion, it is suitable to use anytime, any place and anywhere. It makes our life easier.